The challenges of evaluating business benefits of Information Systems Investments - Khumalo, Nomusa (Department of Information Systems, 2017)
The complexity of evaluating business benefits of Information Systems (IS) Investments stems from the aggregation of business benefits at organisational level, making the correlation of business benefits and IS Investments challenging to ascertain. In an attempt to resolve these correlation challenges, Resource-based Theory was applied to distil drivers of business value of IS investments at process, rather than organisational level. The study employs a qualitative single case study method to promote a shared understanding of the challenges thus faced by practitioners. The findings demonstrate that the extent to which IS capabilities are embedded in business processes further requires disciplined effort and cost to attribute their investment value to business. Thus, the realisation of the business benefits of IS enabled processes was found to be influenced by four key factors; the governance applied to mitigate the risk that would undermine that value, the value judgements made based on accumulated knowledge from prior evaluation challenges; the intricate links between an organisation's IS investment culture and its motivational drivers for what, how and when evaluation should be conducted, and the underlying organisational structures within which those business processes occurred.